The image in early cinema : form and material - Curtis, Scott; Gauthier, Philippe, 1980-; Gunning, Tom, 1949-; Yumibe, Joshua (Early cinema in review., 2018)
"In The Image in Early Cinema, the contributors examine intersections between early cinematic form, technology, theory, practice, and broader modes of visual culture. They argue that early cinema emerged within a visual culture composed of a variety of traditions in art, science, education, and image making. Even as methods of motion picture production and distribution materialized, they drew from and challenged practices and conventions in other mediums. This rich visual culture produced a complicated, overlapping network of image-making traditions, innovations, and borrowing among painting, tableaux vivants, photography, and other pictorial and projection practices. Using a variety of concepts and theories, the contributors explore these crisscrossing traditions and work against an essentialist notion of media to conceptualize the dynamic interrelationship between images and their context."--Publisher description.